Ecuador and Korea: looking for opportunities for economic cooperation. - Yoo, Yeongsik (2012)
The essay shows that the viability of trade relations between Korea and Ecuador depends on the will of the countries to find areas for economic cooperation. The author notes that Ecuador could size the opportunities opened up by the Korean interests in expanding its own export market; in addition, Ecuador could learn from the Korean development experience. In order to support her argument, the author examines the long-term evolution of the relationships between Korea and Ecuador, in particular the trends of trade between the two countries. The essay concludes that there is ample room for improving the economic cooperation between the two countries.